Solusi Pertanian Modern di Tengah Keterbatasan Lahan Pekarangan - Syahputra, Arzanda Jhuan; Febrianty, Novita; Ningrum, Dwi Kusuma; Mumtazah, Ahmad Abim; Asshadiq, Muhammad Daffa; Athari, Naftali Zahra; Alamsyah, Hanum Salsabiella Putri; Fatmawati, Mediana; Al Hudan, Muhammad Niko; Akbar, Akbar; Widodo, Widodo (Universitas Muhammadiyah Yogyakarta, 2025)
This community service program aims to provide modern agricultural solutions for the residents of Dusun Tlogo, Desa Kebonagung, who face limitations in agricultural land. The local community still relies on traditional farming, primarily cultivating rice, while the potential for utilizing home yards remains underutilized. Therefore, this program was introduced as an effort to empower the community, particularly the Women's Farming Group (Kelompok Wanita Tani – KWT) Panti Wicoro, in developing hydroponic systems as a sustainable agricultural alternative. The methods used include theoretical education, practical training, and intensive mentoring in hydroponic implementation. Education is conducted through interactive lectures and group discussions, while practical activities involve the construction of simple hydroponic installations, plant care techniques, and the utilization of organic waste as a growing medium. The results show a significant improvement in participants’ understanding and skills in hydroponics, as evidenced by their ability to independently apply the system. Additionally, this program has the potential to contribute to local food security and better environmental management. It is expected that this agricultural innovation will continue to develop and serve as an inspiration for the community in optimizing home yard utilization through a more efficient technological approach